2015
DOI: 10.1111/jonm.12280
|View full text |Cite
|
Sign up to set email alerts
|

Practice environment and its association with professional competence and work-related factors: perception of newly graduated nurses

Abstract: Management's ability to create and maintain positive practice environments can foster NGNs' professional development and job satisfaction, and consequently retain them in the workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 44 publications
8
73
1
7
Order By: Relevance
“…Other studies of new graduate nurses have found that job satisfaction, professional competence and turnover rates are related to adequate staffing (Numminen et al . , Pineau Stam et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of new graduate nurses have found that job satisfaction, professional competence and turnover rates are related to adequate staffing (Numminen et al . , Pineau Stam et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, nurses’ professional competence is positively related to commitment (Flinkman et al, ) and professional education (Numminen, Leino‐Kilpi, et al, ), but negatively related to the intention to leave the profession (Numminen, Leino‐Kilpi, et al, ; Numminen, Ruoppa, et al, ). In the sense that professional competence results from improvement of professional capabilities, our study also examines the link between professional competence and intention to leave the profession.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, nurses’ actions to improve their professional capabilities may reveal that they perceive that they are likely to use these capabilities indefinitely, indicating reduced turnover intention. Additionally, taking such action should raise care quality (Numminen, Leino‐Kilpi, et al, ; Numminen, Ruoppa, et al, ) and may thus provide job satisfaction, which could in turn reduce turnover intention (Fasbender et al, ). Hence, we hypothesized:…”
Section: Introductionmentioning
confidence: 99%
“…The rural work environment was included in the model in relation to the evidence that supports the potential impact that the work environment may have on competence (Hodge et al, ; Mills et al, ; Numminen et al, ) and confidence (Smith, ; Ulrich et al, ) in practice. For newly graduated nurses in Finland, perceptions of a positive work environment were significantly associated with increased nursing competence (self‐assessed using the 73‐item Nurse Competence Scale), particularly in relation to positive collegial relations, nurse manager abilities, collaboration and leadership (Numminen et al, ). Nurses with lower competence also had less positive perceptions of staffing and resource adequacy compared to nurses with higher perceived competence (Numminen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a comparison of rural and urban nurses enrolled in nurse residency programmes, similar competence between groups was found over time; however, rural nurses were significantly older and had significantly higher job satisfaction and lower job stress when compared to the urban nurses (Bratt et al, ). Job satisfaction has been found to be both an independent and dependent variable related to nursing competence, whereby nursing competence predicted job satisfaction (Walker & Campbell, ), and in combination with age, job satisfaction explained 6.3% of the variance in nursing competence (Numminen et al, ). A potentially more relevant concept to explore in the context of rural nursing practice is level of work engagement.…”
Section: Introductionmentioning
confidence: 99%